Spectroscopic Studies of Methimazole Reactivity toward the Aquapentacyanoferrate (II) Ion in Aqueous Solutions - Cvijanović, D.; Damjanović, V.; Picek, I.; Foretić, B. (Spectroscopy: An International Journal, 2012)
Methimazole (2-mercapto-1-methylimidazole, MMI) and its pentacyanoferrate (II) complex have been characterized by means of UV/Vis, Raman, and NMR spectroscopy. The reaction of MMI with aquapentacyanoferrate (II), [Fe(CN)5(H2O)]3−, in buffered aqueous solutions yielded the [Fe(CN)5(MMI)]3− complex. It was found that only thione tautomer of MMI coordinates to the iron (II). The exceptionally stabile and inert complex was produced.